Strengthening Planning Literature as Human Resources Capacity Improvement through Textbooks for Students of The Department of Public Administration, Faculty of Social Science And Law, State University of Surabaya - Meirinawati, Meirinawati; Fanida, Eva Hany; Niswah, Fitrotun; Oktariyanda, Trenda Aktiva (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2022)
Human resource is one of the main components in the organization, the existence of an organization must also be supported by a high concern for the needs of human resources through a comprehensive, systematic and dynamic planning. Human resources planning is a basic need in every organization as an effort to project various demands in globalization, new technologies, and organizational restructuring processes. Both in terms of quantity, quality, strategy, and good operations, there are at least four aspects of human resource planning that must be considered/done, namely: (1) how many projected number of employees are needed (forecasting of employees), (2) identification of available human resource within the organization (human resource audit), (3) perform an analysis of the balance of supply and deman, (4) run an action program. Strengthening literacy through the preparation of comprehensive teaching materials has an important role in the learning process because it is able to guide students not only to develop their understanding and competence but to instill the character to be adaptive in designing plans according to the demands of needs. Considering the study of the Human Resource Planning Course which is so extensive but has not been supported by the existence of the course textbook. Through the development of textbooks, students are expected to broaden their horizons and ideas through discussions on matters related to Human Resource Planning. The development model that will be used is the ADDIE development model (Analyze, Design, Develop, Implement and Evaluate). It is hoped that the compiled textbooks can instill reinforcement in human resource planning, requiring comprehensive textbooks in theory and practice.